2001
DOI: 10.1603/0022-2585-38.2.188
|View full text |Cite
|
Sign up to set email alerts
|

Selective Oviposition by <I>Aedes aegypti</I> (Diptera: Culicidae) in Response to <I>Mesocyclops longisetus</I> (Copepoda: Cyclopoidea) Under Laboratory and Field Conditions

Abstract: The influence of predacious Mesocyclops longisetus Thiebaud on the selection of oviposition sites by prey Aedes aegypti (L.) was studied under laboratory and field conditions. In both cases, gravid Ae. aegypti females were significantly more attracted to ovitraps containing copepods or to ovitraps with water in which copepods were held previously than to distilled water. Monoterpene and sesquiterpene compounds including 3-carene, alpha-terpinene, alpha-copaene, alpha-longipinene, alpha-cedrene, and delta-cadin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 16 publications
1
41
0
4
Order By: Relevance
“…aegypti than water where M. longisetus was absent. 13 Our data ( Figure 3) show that in northern Vietnam, Mesocyclops survived in outdoor concrete tanks (56-82% positive on average for the 6 communes) and wells (44-59%), but not as well in drums (4-17%) or jars (5-20%). The reason for this may be a paucity of food due to repeated cleaning of drums and jars; in addition, jars (average capacity, 20 L) were emptied regularly for daily household needs.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…aegypti than water where M. longisetus was absent. 13 Our data ( Figure 3) show that in northern Vietnam, Mesocyclops survived in outdoor concrete tanks (56-82% positive on average for the 6 communes) and wells (44-59%), but not as well in drums (4-17%) or jars (5-20%). The reason for this may be a paucity of food due to repeated cleaning of drums and jars; in addition, jars (average capacity, 20 L) were emptied regularly for daily household needs.…”
Section: Discussionmentioning
confidence: 70%
“…They were also questioned about mosquito recognition, biology, and behavior (questions 5-9), the acceptability of various control options, including Mesocyclops (questions [10][11][12][13][14], and the value of different forms of information (question 15).…”
Section: Study Population Six Communes (mentioning
confidence: 99%
“…The overlap in the spatial distribution and habitats of predatory copepods, genus Mesocyclops (Sars), and their aquatic prey, larval stages of Aedes aegypti (Linnaeus), makes them efficacious in dengue vector control (Phong et al 1996, Nam et al 2000, Torres-Estrada et al 2001 or malaria control (Marten et al 1989). Several species of cyclopoids have been used singly (Lardeux 1992, Marten et al 1994, Torres-Estrada et al 2001 or as mixtures of species found to preexist in water storage containers or natural pools (Marten et al 1989, but up until now, the decision about the selection of appropriate candidates has been made in the absence of definitive knowledge of the reproductive potential and longevity of these species.…”
Section: Introductionmentioning
confidence: 99%
“…For example, a strong positive association has been found between An. Albimanus Wiedemann larval abundance and specific vegetation forms of water containing Brachiaria mutica, Cynodon dactylon, Jouveastraminea, Fimbristylis spadicea, and Ceratophyllum demersum [38,67,68]. This suggested that females of this species may be using cues from these plants to select suitable places to lay their eggs.…”
Section: Vegetationmentioning
confidence: 98%
“…Attractant and repellent compounds for mosquitoes oviposition, including anopheline, have been identified from several sources such as hay infusion [18,34], water-associated bacteria [21,35,36], mosquito oviposition and larvae holding water, pheromones [6,21,29,37], and exudates from aquatic competitors or predators [13,38]. The different sources of stimuli result in patterns of distribution of immature-stage mosquitoes that reflect differences in the suitability of sites for the development of different species [29,39].…”
Section: Role Of Habitat Characteristicsmentioning
confidence: 99%